An analysis of the curriculum development to improve literacy skills in islamic elementary school based on hilda taba’s framework - Ahmad Syauqi Fuady; Eka Saptaning Pratiwi; Miftakhur Rizki; Sofan Sulong (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Literacy is an important skill and the foundation for students. Therefore, the school needs to develop a curriculum (planning, implementation, and evaluation) to develop students' literacy skills. This study aims to understand curriculum development to improve literacy skills in Islamic elementary schools. Using a qualitative research approach with a case study design, this study gathers information through interviews with two key informants, analysis of curriculum documents, and observation. The research analysis includes five stages: data collection, coding, data reorganization, data interpretation, and the presentation of findings. Hilda Taba's curriculum development theory serves as a framework for analyzing research data. The results indicate that: (1) the curriculum planning stage is carried out by identifying student needs and exploring community aspirations; (2) the implementation stage of the Madrasah Literacy Movement is realized in the form of a 15-minute daily reading movement, library visits, reading corners, and integration into Indonesian language learning; (3) an evaluation stage once a year to measure the results of curriculum implementation and provide report card for co-curricular activities each semester. The conclusion of this study shows that curriculum development is carried out in a bottom-up manner (grassroots approach) and emphasizes the pivotal role of teachers, as outlined by Hilda Taba.